2022
DOI: 10.4103/jfmpc.jfmpc_1294_21
|View full text |Cite
|
Sign up to set email alerts
|

Study on morbidity pattern among elderly in urban area of Barpeta, Assam, India

Abstract: Background: Degenerative diseases most commonly affect the elderly. The management of these chronic diseases is also very expensive, thereby making it out-of-pocket expenditure for elderly persons. As the elderly population is likely to increase in the future, the concept of active and healthy aging needs to be promoted among the elderly. Objectives: To estimate the morbidity pattern of the elderly in an urban population of Barpeta, and to evaluate the different morbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In our study, we found that older people had much higher rates of abnormalities of the eyes and adnexa, digestive system, circulatory system, and nervous system, than younger people. Pathak G et al [ 15 ] and Shraddha et al [ 16 ] similarly observed that there was a substantial increase in morbidity prevalence with age.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that older people had much higher rates of abnormalities of the eyes and adnexa, digestive system, circulatory system, and nervous system, than younger people. Pathak G et al [ 15 ] and Shraddha et al [ 16 ] similarly observed that there was a substantial increase in morbidity prevalence with age.…”
Section: Discussionmentioning
confidence: 99%
“…Degenerative diseases, or chronic illnesses, commonly affect the elderly population and most of them suffer from multiple medical conditions [5]. Chronic problems which develop gradually induce changes that are not readily reversible, requiring social and other support interventions to complement the treatment of the disease [6].…”
Section: Introductionmentioning
confidence: 99%
“…As the elderly population is likely to increase in the future, there will be a definite shift in the disease pattern, i.e., from communicable to noncommunicable. So, it is high time that the primary health care system gears up for the growing health needs of the elderly in an equitable, optimal, and comprehensive manner [5]. Extensive studies have not been carried out among the vulnerable elderly population in Manipur.…”
Section: Introductionmentioning
confidence: 99%